The Impact of Sports Training on the Spinal Cord Injury Individual’s Balance - Cristina Chieffo; Giorgia Chini; Tiwana Varrecchia; Irene Gennarelli; Alessio Silvetti; Vincenzo Molinaro; Ida Poni; Andrea Mariotti; Simone Tiberti; Annamaria Tamburro; Ilaria Calabrese; Sara Felici; et al. (Sensors)
Spinal cord injury (SCI) causes major challenges to mobility and daily life activities and maintaining balance becomes a crucial issue. Individuals with SCI often need to adopt new strategies to manage balance with minimal discomfort. Sports and physical activities have become one of the most popular rehabilitation methods for people with SCI. The assessment of balance improvement currently relies on subjective evaluation scales, and this study aims to quantitively assess the efficacy of sports on the balance strategies of people with SCI. Twenty-two SCI people remained seated still for 30 s, with their eyes open and closed, and we recorded trunk kinematics with an optoelectronic system before and after a three-months sports program. We also computed trunk total sway length, mean velocity, and sway density curve. Statistical analyses were performed to compare SCI people before and after the rehabilitation program and to investigate any correlations between the trunk balance parameters and the clinical scales. The results demonstrate improvements in static balance, with significant reductions in sway length and mean velocity. In conclusion, our findings confirm the potential of sports to enhance balance in SCI individuals and suggest that integrating structured sports programs into rehabilitation can improve stability and postural control.